Analisis Prestasi Belajar Mahasiswa Jurusan Akuntansi Politeknik Negeri Banjarmasin Ditinjau dari Asal Sekolah - Priyougie; Haq, Ahsanul (Indonesian Journal of Applied Accounting and Finance, 2023)
Learning achievement is not limited by school origin, but various factors can play a role including persistence, family support, and the social environment outside of school. This research aims to analyze the learning achievement of students majoring in Accounting at the Banjarmasin State Polytechnic in terms of school origin. The school origin of students entering this department is divided into three types, namely: High School (SMA), Vocational High School (SMK) and Madrasan Aliyah (MA). Students from these three types of schools experience the same treatment in the learning process. There are no special classes and they have the same assessments which includes attendance, behavior, assignment, mid-semester exam and final semester exam for every course taught. The results of the research show that the average GPA of students from SMA with 66 people was 3.58, the average GPA of students from SMK with 34 people was 3.64, while the average GPA of students from MA with 19 people -the average is 3.50. The highest average GPA is for students from vocational schools. From the Anova statistical test, it was found that: 1) there was no significant difference between the GPA of groups of students from SMA and SMK with the Sig value. 0.116 > 0.05; 2) there is a significant difference between the GPA of groups of students from SMA and MA because the Sig value. 0.023 < 0.05; and 3) there is a significant difference between the GPA of the group of students from SMK and MA because the value of Sig.0.022 < 0.05.